PELANGGARAN LALU LINTAS MENURUT HUKUM POSITIF DAN HUKUM ISLAM DI KOTA MEULABOH KABUPATEN ACEH BARAT - T Muhajir; Sumardi Efendi; Syaibatul Hamdi (UIN Mahmud Yunus Batusangkar, 2023)
Traffic rules primarily aim to ensure comfort and safety during driving. Unfortunately, many individuals still disregard these rules, causing significant losses to both themselves and others. This issue is highly critical, especially in major cities like Meulaboh. This research focuses on the position of traffic violators in positive law and Islamic law, as well as efforts to address and reduce traffic violations in Meulaboh. The study employs field research methodology with an empirical juridical approach that analyzes the application of law in society. The research results indicate a high level of traffic violations in Meulaboh due to the lack of legal awareness among the community regarding traffic regulations. Common violations include running red lights, not wearing helmets, not using vehicle lights, not carrying necessary documents while driving, going against the traffic flow, disregarding traffic signs, not using vehicle mirrors, and driving on sidewalks. From the perspectives of positive law and Islamic law, a Muslim is prohibited from violating traffic regulations as it may endanger oneself and others. These regulations are established to prevent risks and provide benefits to Muslims, as well as to avoid any potential harm.